The Influence of Communication Media and Interpersonal Communications on Company Performance at Koja Utara Ptikemas Terminal - Mohamad Arief Budiana; Jamalulail Jamalulail (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the influence of communication media and interpersonal communication on company performance at Koja Container Terminal, North Jakarta. The research population is all employees at Koja Container Terminal, North Jakarta. This research uses a quantitative method with survey type using google form. The research population is all employees at Koja Container Terminal, North Jakarta. The sampling technique was probability sampling with simple random sampling, through the Slovin formula, 89 samples were obtained. The research trial consisted of 30 respondents outside the research sample. . The results showed that there was a positive and significant influence partially and simultaneously on communication media and interpersonal communication on company performance at Koja Container Terminal, North Jakarta. The conclusion of the study shows that if you want to improve the company's performance, then factors such as communication media and interpersonal communication need to be improved as well. The implications of the company's research at the Koja Container Terminal, North Jakarta are making policies related to the application of communication media and interpersonal communication to company performance.